1978
DOI: 10.1111/j.1600-0722.1978.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the formation of dental plaque and gingivitis in humans by crude mutanase

Abstract: The effect of a Trichoderma harzianum enzyme preparation containing mutanase (a-1,3 glucan glucanohydrolase) on plaque accumulation and composition and on occurrence of gingivitis was assessed in 20 persons in a double-blind cross-over investigation. The enzyme preparation was administered in chewing gum. Two test periods ol 1 week were preceded by scaling and cleansing of the teeth, oral hygiene instruction, and controlled hygiene for at least 3 weeks. Oral hygiene measures were discontinued during the test p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…The reaction was terminated by adding 0.1 ml of 0.4 M NaOH and the samples were centrifuged for 5 min at 14,000 ϫ g and filtered through 0.45-m HV-filters (Millipore). To each filtrate (100 l) in Eppendorf vials 750 l of ferricyanide reagent (0.4 g/liter K 3 Fe(CN) 6 , 20 g/liter Na 2 CO 3 ) was added and incubated 15 min at 85°C. After allowing the samples to cool, the decrease in absorbance at 420 nm was measured.…”
Section: Expression Of Recombinant T Harzianum Mutanase In a Oryzae-mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was terminated by adding 0.1 ml of 0.4 M NaOH and the samples were centrifuged for 5 min at 14,000 ϫ g and filtered through 0.45-m HV-filters (Millipore). To each filtrate (100 l) in Eppendorf vials 750 l of ferricyanide reagent (0.4 g/liter K 3 Fe(CN) 6 , 20 g/liter Na 2 CO 3 ) was added and incubated 15 min at 85°C. After allowing the samples to cool, the decrease in absorbance at 420 nm was measured.…”
Section: Expression Of Recombinant T Harzianum Mutanase In a Oryzae-mentioning
confidence: 99%
“…Mutan is composed of ␣1,3-glucan with some ␣1,6-glucan (dextran) side chains. Mutanase (␣1,3-glucanase, EC 3.2.1.59) and dextranase (␣1,6-glucanase, EC 3.2.1.11) enzymes could be beneficial additives to dentifrice preparations as it has been shown that these enzymes are capable of removing biofilms created by oral bacteria in vitro (4) and reducing plaque formation in vivo (5,6). Mutanase activity from the filamentous fungus Trichoderma harzianum was first described by Guggenheim and Haller (7).…”
mentioning
confidence: 99%
“…In addition to its possible medical applications against dental caries (17,20,24), important agricultural applications can be envisaged for this enzyme. Overexpression in recombinant T. harzianum could result in the generation of more effective biocontrol strains.…”
mentioning
confidence: 99%
“…Mutanases were isolated and characterized biochemically, and some of them were tested regarding caries-preventive efficacy (14,15,19,21,22,35). However, mutanase RM1 can be readily differentiated from all of these previously reported enzymes as documented in the present study.…”
Section: Discussionmentioning
confidence: 99%